Matrículas de estudantes com deficiência na EJA e a oferta do atendimento educacional especializado em municípios paulistas - Santos, Flávia Maria dos (2019)
Special education in the modality of youth and adult education is part of the process of including people who were doubly excluded from society. In this theme, the analysis of factors that make up this reality, allows realities to be exposed and that from there, the different aspects that make up this modality are studied.The general purpose of the research is to characterize the general enrollment of PAEE students in EJA (elementary school level) in São Paulo municipal schools and to identify the offer of AEE for PAEE students enrolled in the EJA modality in ten cities of São Paulo state. The survey was organized in two stages. Stage 1 was characterized by data collection at INEP and fil-tering by the IBM SPSS Statistics 20 software, and Stage 2 by analysis and discussion of the collected data, this stage was split into the categories: general analysis of PAEE students' enrollments at EJA in SP; analysis of the enrollment of PAEE students in EJA in municipal schools in the 10 selected cities; analysis of enrollments according to the types of disabilities; characterization of the enrollment of municipal schools in the 10 cities of the study and analysis of the offer of AEE in the 10 cities. Findings indicated that variation in the number of enrollments between the four years studied (2015 to 2018). In the characterization of the cities selected for the study, there was a predomi-nance of enrollments of white, male and predominant age groups (15 to 20 and from 21 to 30 years old) in the enrollments analyzed. In the AEE offer, the data obtained reveal the discrepancy between the numbers of enrollments counted with the number of services provided to these students, according to the survey in the ten cities selected for this research.